Spatial patterns and impacts of slope failures in five canyons of the Teton Mountains, Grand Teton National Park, Wyoming - Butler, William David (Kansas State University, 2013)
Slope failures play a significant role as a mass movement hazard in the deglaciated mountain canyons in Grand Teton National Park. The park’s geologic and glacial histories are unique in comparison to other areas in the Rocky Mountain range. However, few detailed maps and statistical analyses of slope failures as hazards exist for park officials and visitors. The purpose of this study is to produce a comprehensive map of slope failures in five of the most accessible and commonly used canyons of the park: Cascade, Death, Garnet, Granite, and Paintbrush. This project combined fieldwork, LiDAR imagery, and GIS mapping to document five main categories of slope failures—rock slides, rock/debris flows, rock falls, and snow avalanches, as well as complex slope failures involving a combination of these categories. Summary statistics, maps, and histograms of average slope gradient, aspect, and curvature conditions as well as precipitation conditions at the “source” area of slope failures were generated for individual canyons as well as the entire study area. Snow avalanche source areas where debris flows were not readily present occurred most commonly on north and northeast facing slopes, slopes averaging a 40% gradient, and slightly convex slopes. Debris flow source areas occurred most commonly on south and southeast facing slopes, slopes with an average 42% gradient, and on slightly convex slopes. Rock fall source areas were most common on north facing slopes, slopes of an average 55% gradient, and a mostly flat curvature. Rock slide source points were most common on north facing slopes, slopes of an average 54% gradient, and flat to slightly concave slopes. Rock Mass Strength (RMS) values were sampled at a rate of every 0.5 kilometers on the hiking trail of each canyon to provide an introductory insight into rock stability conditions in each canyon. Slope failures not only impact the physical landscape of canyons in Grand Teton National Park but can affect human structures as well. Physical attributes and locations of slope failures were compared to locations of camping zones and hiking trails in the Park to determine areas of common human usage that were most susceptible to past movement events.
Keywords: Geomorphology; Geographic Information Systems; Mass movement; Natural hazards; Geographic Information Science and Geodesy (0370); Geomorphology (0484)